Veno‐arterial extracorporeal membrane oxygenation for COVID‐19‐associated acute myocardial injury complicated by refractory cardiogenic shock. Issue 11 (15th August 2021) - Flagiello, Michele; Al Harthy, Ahmed; Boccalini, Sara; Jacquemet, Louis; Obadia, Jean F.; Baudry, Guillaume; Pozzi, Matteo
Abstract: Cardiovascular system involvement and its negative prognostic impact have been increasingly identified in coronavirus disease 2019 (COVID‐19) patients. Optimal medical treatment allows for safe management of most of these cardiovascular presentations while COVID‐19‐associated refractory cardiogenic shock could be rescued by veno‐arterial extracorporeal membrane oxygenation (VA‐ECMO). We present a case of acute myocardial injury related to COVID‐19 complicated by refractory cardiogenic shock and treated by VA‐ECMO implantation.